2022
DOI: 10.24136/oc.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of international opportunity recognition processes on problem-solving competence: how does past negative entrepreneurial experience matter?

Abstract: Research background: Little research addresses how identifying an opportunity in the international market, whether through active search or serendipitous discovery, may have implications for the subsequent gestation behaviors. An emerging body of research suggests addressing this deficiency by focusing on the cognitive and experience-based factors that international entrepreneurs use to develop an opportunity in the foreign market once identified. Purpose of the article: The aim of this study is to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…By examining the drivers of corporate sustainability, the study found that dynamic capabilities to sense opportunities, reconfigure, organizational flexibility, and technological flexibility lead to competitive advantage development. Ferreira et al (2020) research shows that a firm's competitiveness is higher when creativity and innovation capabilities are supported by a higher level of entrepreneurial orientation, which supports critical firm interests in seeking new market opportunities and renewing existing areas of operation (Terán-Yépez et al, 2022). Other quantitative studies indicate that the innovative behavior of an organization and its environmental dynamism has a significant positive impact on competitive advantage (Fatoki, 2021;Ključnikov et al, 2021;Civelek et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 94%
“…By examining the drivers of corporate sustainability, the study found that dynamic capabilities to sense opportunities, reconfigure, organizational flexibility, and technological flexibility lead to competitive advantage development. Ferreira et al (2020) research shows that a firm's competitiveness is higher when creativity and innovation capabilities are supported by a higher level of entrepreneurial orientation, which supports critical firm interests in seeking new market opportunities and renewing existing areas of operation (Terán-Yépez et al, 2022). Other quantitative studies indicate that the innovative behavior of an organization and its environmental dynamism has a significant positive impact on competitive advantage (Fatoki, 2021;Ključnikov et al, 2021;Civelek et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 94%
“…SEM method is very often used to evaluate quantitative researches in a given issue e.g. (Teran-Yepez et al, 2022;Chang et al, 2022;Maloku et al, 2021). The structured equation modelling was used for quantification, verification and visualisation relationship between factors (FMS, CEB, CSR).…”
Section: Methodsmentioning
confidence: 99%
“…Through education, it will form entrepreneurial souls in students (Tanwir et al, 2020). Someone who has competence in entrepreneurship will be faster in overcoming business problems so that it will be easy to achieve success in business (Terán-Yépez et al, 2022).…”
Section: Entrepreneurial Competencementioning
confidence: 99%